Profiling DNA Ligase Substrate Specificity with a Pacific Biosciences Single‐Molecule Real‐Time Sequencing Assay. Issue 3 (7th March 2023) - Duckworth, Alexander T.; Bilotti, Katharina; Potapov, Vladimir; Lohman, Gregory J. S.
Abstract: DNA ligases catalyze the joining of breaks in nucleic acid backbones and are essential enzymes for in vivo genome replication and repair across all domains of life. These enzymes are also critically important to in vitro manipulation of DNA in applications such as cloning, sequencing, and molecular diagnostics. DNA ligases generally catalyze the formation of a phosphodiester bond between an adjacent 5′‐phosphate and 3′‐hydroxyl in DNA, but they exhibit different substrate structure preferences, sequence‐dependent biases in reaction kinetics, and variable tolerance for mismatched base pairs. Information on substrate structure and sequence specificity can inform both biological roles and molecular biology applications of these enzymes. Given the high complexity of DNA sequence space, testing DNA ligase substrate specificity on individual nucleic acid sequences in parallel rapidly becomes impractical when a large sequence space is investigated. Here, we describe methods for investigating DNA ligase sequence bias and mismatch discrimination using Pacific Biosciences Single‐Molecule Real‐Time (PacBio SMRT) sequencing technology. Through its rolling‐circle amplification methodology, SMRT sequencing can give multiple reads of the same insert. This feature permits high‐quality top‐ and bottom‐strand consensus sequences to be determined while preserving information on top‐bottom strand mismatches that can be obfuscated or lost when using other sequencing methods. Thus, PacBio SMRT sequencing is uniquely suited to measuring substrate bias and enzyme fidelity through multiplexing a diverse set of sequences in a single reaction. The protocols describe substrate synthesis, library preparation, and data analysis methods suitable for measuring fidelity and bias of DNA ligases. The methods are easily adapted to different nucleic acid substrate structures and can be used to characterize many enzymes under a variety of reaction conditions and sequence contexts in a rapid and high‐throughput manner. © 2023 New England Biolabs and The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Preparation of overhang DNA substrates for ligation Basic Protocol 2 : Preparation of ligation fidelity libraries Support Protocol 1 : Preparation of ligation libraries for PacBio Sequel II sequencing Support Protocol 2 : Loading and sequencing of a prepared library on the Sequel II instrument Basic Protocol 3 : Computational processing of ligase fidelity sequencing data